ChemInform Abstract: Palladium(II)‐Catalyzed Sequential C—Cl Bond Formation: A Novel and Efficient Method for Direct α, α‐Dichlorination of β‐Dicarbonyl Compounds. Issue 6 (11th February 2014) - Liu, Weibing; Tan, Liquan; Zhou, Peng; Chen, Cui; Zhang, Qing
Abstract Reaction conditions are optimized for the selective α, α‐dichlorination of N‐substituted acetoacetamides and the process is investigated with a series of related substrates.